Dynamics of the Legal Environment and the Development of Communal Irrigation Systems. Issue 1 (3rd March 2022) - Smith, Steven M.
The success of local user groups managing communal natural resources depends to a great degree on external factors such as the legal environment. However, depending on their political power, the local users may exert some influence on the legal environment. This creates important dynamics between external legal factors and local resources governance. To explore this path dependent dynamic in common property resources, I conduct a historical case study of the development and legal transitions of acequias (irrigation ditches) in modern day New Mexico, US. Initially colonized by Spain in 1598, acequias have been developed and used for irrigation even as the region transferred from Spanish to Mexican to US sovereignty. The biggest legal changes occurred during the US territorial period (1851–1912), and I draw on the primary sources in the New Mexico Territorial Archives to better understand the origin, evolution, and motivation of irrigation statutes. I combine this with data on the timing of acequia and other irrigation enterprises development in New Mexico to show how the legal rules influence new development and how that new development shifts the vested interests and political coalitions, influencing future legal changes. The historical perspective highlights that external factors are important, but also that those factors are not entirely independent from the local systems: dynamic feedback loops create path dependence, in this case producing an incremental loss of local governance and power.